Crude oil and refined products transportation from the Caspian region to the European Union - Akhmedov, Erjan (Acta Technica Jaurinensis, 2021)
This article provides in-depth description of the situation with crude oil and refined products transportation from the Caspian Region to the European Union. It describes demand and supply, main transportation routes and modes of transport. The article then addresses existing and potential issues and discusses the ways to resolve them. There are two knowledge gaps associated with the topic of this article: (i) transportation of crude oil and refined products from the Caspian region to the European Union receives limited attention of researchers, and (ii) the majority of related scientific publications consider mainly the aspects of geopolitics and the European energy security, but not the transportation itself. The author attempts to partially close these gaps.